Developing an Instrument to Capture Multifaceted Visitor Experiences: The DoVE Adjective Checklist. Issue 2 (3rd July 2018) - Packer, Jan; Ballantyne, Roy; Bond, Nigel
Abstract: Understanding visitor experiences is an important focus for visitor research in attractions such as museums, zoos, and heritage sites because the visitor experience is the core product of the interaction between the visitor and the activities, events, and environments they encounter. This article describes the development of an instrument designed to capture multiple facets of the visitor experience using a simple and unobtrusive adjective checklist. The checklist has been tested and used at a range of attractions, including museums, art galleries, science centers, zoos, and aquariums. The instrument allows visitors' responses to the experiential offerings of each site to be captured and graphically displayed, as well as providing individual measures on 15 dimensions. The instrument can be used to support further research and theory development as well as exhibit design and evaluation. Examples of such applications are discussed.